Pengaruh Keefektifan Penerapan Sistem Pengendalian Internal, Asimetri Informasi, Dan Keadilan Distributif Terhadap Kecendrungan Kecurangan (Fraud) Pada Bumdes Se-Kecamatan Gerokgak - Luh Putu Debby Cinthya Dewi; I Made Pradana Adiputra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This research aims to determine the effect of the effectiveness of the implementation of the internal control system, information asymmetry, attributive to the tendency of fraud (fraud) in BUMDes in Gerokgak District. This research is a quantitative research. Primary data used in this study were obtained from questionnaires and measured using a Likert scale. The population used in this study is the management of 11 BUMDes in Gerokgak District. The sampling technique uses a purposive sampling method that has BUMDes criteria that are still active until 2020, and the BUMDes management consists of the Chairperson, Secretary, Treasurer, and business unit sections. Based on these criteria a sample of 66 respondents was obtained. The data analysis technique used is multiple linear regression analysis using SPSS version 25.0 for Windows.The results of this study indicate that: (1) the effectiveness of implementing an internal control system has a significant negative effect on fraud, (2) information asymmetry has a significant positive effect on fraud, and (3) distributive justice has a significant negative effect on trends fraud (fraud).